A comparison between the therapeutic effects of Conbercept combined with panretinal photocoagulation and panretinal photocoagulation monotherapy for high-risk proliferative diabetic retinopathy - Sun, Yaoyao; Qi, Huijun (Frontiers in Endocrinology, 2023)
OBJECTIVE: To compare the therapeutic effects of the administration of intravitreal Conbercept (IVC) plus panretinal photocoagulation (PRP) to that of PRP monotherapy in patients with high-risk proliferative diabetic retinopathy (PDR). METHODS: In this retrospective consecutive case series, we analyzed the data on high-risk PDR patients followed up for 12 months. Patients were divided into two groups: the IVC+PRP group and the PRP monotherapy group. Patients in the IVC+PRP group were initially administered 3 IVC injections and PRP, while patients in the PRP monotherapy group received PRP only. Depending on the grouping criteria, patients in both groups were administered either IVC+PRP or PRP only if the neovascularization (NV) did not regress. From the initiation to month 12 of treatment, we recorded and compared the data on the NV regression rate, improvement in best-corrected visual acuity (BCVA), laser spots, changes in central macular thickness (CMT), complications, and the need for vitrectomy for all patients. RESULTS: In this study, 79 eyes of 58 patients in the IVC+PRP group and 86 eyes of 60 patients in the PRP monotherapy group were included. During the follow-up of 12 months, the number of eyes with complete regression, partial regression, and no regression or increase in NV were 56 (70.88%), 23 (29.12%), and 0 (0%) in the IVC+PRP group and 13 (15.12%), 50 (58.14%), and 23 (26.74%) in the PRP group (p < 0.001). The BCVA was significantly higher and CMT was lower in the patients of the IVC+PRP group than in the PRP monotherapy group at 3, 6, and 12 months of follow-up (p < 0.05). The mean number of laser spots was lower in the patients of the IVC+PRP group than in the PRP group (1,453 ±87 spots vs. 2,267 ±94 spots, p < 0.05). A significantly lower percentage of patients in the IVC+PRP group underwent vitrectomy than that in the PRP group (7 (8.86%) vs. 27 (31.40%), p < 0.001). CONCLUSION: High-risk PDR patients treated with IVC + PRP showed a higher rate of NV regression, more effective improvement in the BCVA, and lower vitrectomy rate compared to those who were administered PRP monotherapy.